DAMPAK GAME MOBILE LEGEND TERHADAP INTERAKSI SOSIAL MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS MUHAMMADIYAH JEMBER ANGKATAN TAHUN 2020 - Iqbal Nafi’ul Firdaus; M.H. Thamrin (Universitas Muhammadiyah Jember, 2023)
This research aims to investigate the impact of Mobile Legends game factors on the tendency of 2020 students of the Communication Science study program at Muhammadiyah University of Jember class of 2020 to play. The factors studied include ease of access and play, simple and interesting gameplay, and the presence of multiplayer features in the game. This research was conducted using qualitative methods by collecting data through interviews with 5 student respondents. The research results show that the Mobile Legends game factors, namely easy to access and play, simple and interesting gameplay, and multiplayer features, have a significant impact on the tendency of students in the Communication Sciences study program to play. These factors create a fun gaming experience, facilitate participation, and provide opportunities for social interaction and collaboration in the game. However, this research also reveals that there are negative impacts such as differences of opinion, conflict and toxic behavior in the gaming community. The use of Mobile Legends can also affect the quality and length of student social interaction in the real world. This research provides an in-depth understanding of how Mobile Legends game factors influence Communication Science students' tendencies to play and its impact on their social interactions. The implications of these findings can help in further understanding the use of games in college students' academic and social contexts.